#TITLE_ALTERNATIVE# - Dwi Kurniawan (NIM : 13613012), Andik
Transportation is closely related to human life. One of the most widely used in Indonesia is train. One of the train that has an important role in maintaining quality of railway infrastructure is measuremet train. The function of this train is to measure and test the railway infrastructure, such as rails and pantographs. This researchÃ‚Â’s aim is to analyze the strength of Sulawesi measurement train (1435) carbody structure developed by PT. INKA Madiun. The structural strength of a transportation is very important, because it is directly related to the safety of equipment, passengers, and environment. The regulation of feasibility of the structure becomes a step that must be met and approved before the structure is used for trains. In this research, a numerical simulation study was conducted based on Test Method for Statics Load of Body Structures of Railway Rolling Stock JIS E7105-1989 standard and Peraturan Menteri Perhubungan Nomor : KM. 41 Tahun 2010. The validation of simulation data is obtained by convergence test on finite element. The numerical simulation study include static load cases based on standard and quasi-static loading case where the load exceeds the standard. Quasi-static load case will be represented by vertical full load with 250 tons compression. The simulation is done with two model that is full shell element model and combined shell-beam element model. Those models will be compared to obtain the most effective and efficient to use. The result of simulation at static case show that the structure of measurement train generally meet the acceptance criteria, because the stress occurs still under 75% yield strength material. But, the structure has undergone plastic deformation when it gived by static load at vertical axis with 100 tons compression, fillet of train door is the component which plastic deformation ocurred. On deflection criteria for vertical load, the deflection occurs, but still comply the acceptance criteria. The result of simulation at quasi-static case shows the structure of measurement train is not meet on structural crashworthiness criteria, because the damage is not occur at train cabin but at the door structure of train. Comparison between full shell element model and shell-beam element model shows that the shell-beam element model takes less time for modelling and computation.